Use of Selective Serotonin-Reuptake Inhibitors during Pregnancy and the Risk of Clubfoot - Yazdy, Mahsa M (2014)
BACKGROUND: Selective serotonin-reuptake inhibitors (SSRIs) are the most commonly prescribed anti depressants. Previous studies have suggested that SSRIs may increase the risk of birth defects, including clubfoot. Using data from a population-based case-control study, we evaluated whether SSRI use increased the risk of clubfoot. METHODS: Mothers were interviewed within one year after delivery about sociodemographic factors, pregnancy events and exposures. They were specifically asked if they experienced depression or anxiety or if they took any of the following SSRIs: citalopram, escitalopram, fluvoxamine, paroxetine, sertraline or fluoxetine. We used logistic regression models to calculate odds ratios (ORs) and 95% confidence intervals. RESULTS: We included a total of 622 clubfoot cases and 2002 non-malformed controls born between 2006 and 2011 in Massachusetts, New York, and North Carolina. For the second or third lunar month of pregnancy (the relevant gestational period), SSRI use for a period of more than 30 days was higher in case mothers (5%) than control mothers (3%). After adjustment for maternal smoking and body mass index, the OR for any SSRI use and clubfoot was 1.8 (95% confidence interval=1.1–2.8). When individual SSRIs were examined, ORs were elevated for sertraline (1.6 [0.8–3.2]), paroxetine (9.2 [0.7–484.6]) and escitalopram (2.9 [1.1–7.2]). CONCLUSION: Our data suggest an increased risk of clubfoot occurrence in relation to SSRI use. Drug-specific risks varied widely and some estimates were unstable.